Electrochemical corrosion behavior of 2205 duplex stainless steel in hot concentrated seawater under vacuum conditions. (1st April 2020) - Yang, Yong; Zeng, Hongtao; Xin, Sensen; Hou, Xueling; Li, Moucheng
Highlights: The polarization resistance, passive film composition and oxygen reduction reaction markedly change with the vacuum degree. The pitting potential decreases linearly with the vacuum pressure until the appearance of violent boiling in the solution. The pressure reduction and solution boiling enhance occurrence and repassivation tendencies of stable pitting corrosion. Abstract: The corrosion behavior of 2205 duplex stainless steel (DSS) was investigated in the hot concentrated seawater under vacuum pressures by using electrochemical measurement techniques. The vacuum pressure results in the decrease of dissolved oxygen concentration and even boiling of solution. 2205 DSS passivates spontaneously under various vacuum pressures. The vacuum pressures (no lower than 28.4 kPa) greatly influence the polarization resistance, passive film composition and oxygen reduction reaction. The pressure reduction and the violent boiling of solution distinctly decrease the pitting potential, but increase the repassivation potential. They may enhance both the occurrence and repassivation tendencies of stable pitting corrosion.